From Latin America to Israel: the Story of Postwar Argentinian Jewish Immigration (KULT_online, 2018)
This monograph from Sebastian Klor explores the story of Jewish immigration from Argentina to Israel. Klor sets the establishment of the State of Israel in 1948 and the Six Day War as caesura that form the beginning and end of his research. Between Exile and Exodus explores changing political and economic conditions in Argentina in Israel, and concludes that the factors influencing the emigration were diverse and were not clearly bound to Argentinian anti-Semitism or Zionist dreams. Klor portrays Argentinian emigration to Israel as any other form of migration, and suggests not viewing the aliyah (ascent in Hebrew, the way immigration to Israel is described) as an exceptional case.